Molecular Functions of Thyroid Hormones and Their Clinical Significance in Liver-Related Diseases. (26th June 2013) - Chi, Hsiang Cheng; Chen, Cheng-Yi; Tsai, Ming-Ming; Tsai, Chung-Ying; Lin, Kwang-Huei
Abstract : Thyroid hormones (THs) are potent mediators of several physiological processes, including embryonic development, cellular differentiation, metabolism, and cell growth. Triiodothyronine (T3 ) is the most biologically active TH form. Thyroid hormone receptors (TRs) belong to the nuclear receptor superfamily and mediate the biological functions of T3 via transcriptional regulation. TRs generally form heterodimers with the retinoid X receptor (RXR) and regulate target genes upon T3 stimulation. Research over the past few decades has revealed that disruption of cellular TH signaling triggers chronic liver diseases, including alcoholic or nonalcoholic fatty liver disease and hepatocellular carcinoma (HCC). Animal model experiments and epidemiologic studies to date imply close associations between high TH levels and prevention of liver disease. Moreover, several investigations spanning four decades have reported the therapeutic potential of T3 analogs in lowering lipids, preventing chronic liver disease, and as anticancer agents. Thus, elucidating downstream genes/signaling pathways and molecular mechanisms of TH actions is critical for the treatment of significant public health issues. Here, we have reviewed recent studies focusing on the roles of THs and TRs in several disorders, in particular, liver diseases. We also discuss the potential therapeutic applications of THs and underlying molecular mechanisms.